The oncological outcome after right hemicolectomy and accuracy of CT scan as a preoperative tool for staging in right sided colonic cancers. (25th April 2013) - Lim, M.; Hussain, Z.; Howe, A.; Storey, R.; Petty, D.; Haselden, J.; Sebag‐Montefiore, D.; Alexander, D.
Abstract Aim Neoadjuvant chemotherapy may have a role in the management of colonic carcinoma but clinical trials are required to determine whether this approach is superior to the standard policy of radical surgery, high‐quality histopathology and selective postoperative chemotherapy. The selection of appropriate patients for such trials will depend on accurate locoregional staging of disease by preoperative CT scanning. We studied the outcome after radical right hemicolectomy and assessed the accuracy of preoperative CT scans in the prediction of postoperative pathology. Method A retrospective analysis of right hemicolectomies performed with curative intent for colon cancer under the care of a single colorectal surgeon (D.J.A.) was performed. Preoperative CT‐proven Dukes D patients were excluded. Patient demographics, postoperative histology, use of adjuvant chemotherapy and survival data were collected. Kaplan–Meier curves were constructed and log‐rank testing was performed to compare cancer‐specific survival. Fifty patients had their preoperative CT scan images reviewed by two radiologists both blinded to the results of the postoperative histology. The accuracy of preoperative CT for T and N staging was studied. A P‐value of < 0.05 was significant. Results There were 136 patients (79 women). Median age was 76 (interquartile ratio 67–82) years. Median period of follow‐up was 72 (interquartile ratio 39–92) months. There were 56 deaths (39 medical, 16 oncological and 1 postoperative). There were three groups of patients: node negative (n = 84), node positive with postoperative adjuvant chemotherapy (n = 30) and node positive without chemotherapy (n = 22). Five‐year cancer‐specific survival for node negative disease was 84% and was poorer for node positive patients who received adjuvant chemotherapy when compared with those who did not (62 vs 72%, P‐value = 0.046 on log‐rank testing). Sensitivity, specificity, positive and negative predictive value of CT scan for tumour (T) stage were 90, 33, 86 and 43% respectively, while that for nodal (N) stage was 83, 38, 57 and 69%, respectively. Conclusion CT scan has limited accuracy in predicting those patients with advanced locoregional disease who might benefit from neoadjuvant treatment. When this finding is combined with relatively high cancer‐specific survival with surgery alone the impact of adjuvant chemotherapy on survival after radical surgery for right colon carcinoma may be marginal.